Matrix Metalloproteinases-7 and Kidney Fibrosis - Ke, Ben; Fan, Chuqiao; Yang, Liping; Fang, Xiangdong (Frontiers in Physiology, 2017)
Matrix metalloproteinase-7 (MMP-7) is a secreted zinc- and calcium-dependent endopeptidase that degrades a broad range of extracellular matrix substrates and additional substrates. MMP-7 playsa crucial role in a diverse array of cellular processes and appears to be a key regulator of fibrosis in several diseases, including pulmonary fibrosis, liver fibrosis, and cystic fibrosis. In particular, the relationship between MMP-7 and kidney fibrosis has attracted significant attention in recent years. Growing evidence indicates that MMP-7 plays an important role in the pathogenesis of kidney fibrosis. Here, we summarize the recent progress in the understanding of the role of MMP-7 in kidney fibrosis. In particular, we discuss how MMP-7 contributes to kidney fibrotic lesions via the following three pathways: epithelial-mesenchymal transition (EMT), transforming growth factor-beta (TGF-β) signaling, and extracellular matrix (ECM) deposition. Further dissection of the crosstalk among and regulation of these pathways will help clinicians and researchers develop effective therapeutic approaches for treating chronic kidney disease.